(untitled) (Journal of Advanced Research in Social Sciences, 2022)
Up to date myths are regarded as universal and enduring for their depicting human’s understanding and knowledge. It presents clues and intimations to Man’s origins of belief and life. Harry Potter, a series of storytelling written by J.K. Rolling, is a metaphoric presentation of myths and cultural background behind each one of them. This study investigates and explores how J.K. Rolling involves in origins of cultural textually while sharing mythological ideas in modern literature as a creative way to give new senses to each of them. With its unique demonstration, Harry Potter places an outstanding position in giving myth a new dimension and ties ancient with present via a new style of mythmaking in modern literature. The study conducts an analytic explanation of the importance of mythmaking to literature in general and specifically in Harry Potter. The findings that the study arrives at are that myths are true replications of cultures and societies, and Rolling’s stories make new connection with the depth of human superficiality as well as it renders the possibility to revive mythological mentality in modern era.